P Is Available and K Is Available in Tatelu Rondor Village - Simaremare, Septi Maimunah (Soil and Environment Journal, 2024)
Available P shows moderate criteria with an average value from the South, Central, North, East, and West location points of 18.304 ppm. For K-available with varying values, namely in the 0-20 cm layer it ranges from 24.22 ppm to 26.11 ppm, and at > 20 cm it ranges from 23.12 ppm to 25.67 ppm. Keywords: Plant-available, nutrient, Phosphorus, and Potassium Abstrak P-tersedia menunjukkan kriteria sedang dengan nilai rata-rata dari titik lokasi Selatan, Tengah, Utara, Timur, dan Barat sebesar 18,304 ppm. Untuk K-tersedia dengan nilai yang bervariasi, yaitu pada lapisan 0-20 cm berkisar antara 24,22 ppm sampai dengan 26,11 ppm, dan pada > 20 cm berkisar antara 23,12 ppm sampai dengan 25,67 ppm. Kata kunci: Ketersediaan tanaman, hara, Fosfor, dan Kalium